Utilization of Group-Based, Community Acupuncture Clinics: A Comparative Study with a Nationally Representative Sample of Acupuncture Users - Chao, Maria T. (Mary Ann Liebert, Inc., 2012)
OBJECTIVES: Acupuncture utilization in the United States has increased in recent years, but is less common among racial/ethnic minorities and those of low socioeconomic status. Group-based, community acupuncture is a delivery model gaining in popularity around the United States, due in part to low-cost treatments provided on a sliding-fee scale. Affordable, community-based acupuncture may increase access to health care at a time when increasing numbers of people are uninsured. To assess the population using local community acupuncture clinics, sociodemographic factors, health status, and utilization patterns compared to national acupuncture users were examined. DESIGN: Data were employed from (1) a cross-sectional survey of 478 clients of two community acupuncture clinics in Portland, Oregon and (2) a nationally representative sample of acupuncture users from the 2007 National Health Interview Survey. RESULTS: Portland community acupuncture clients were more homogeneous racially, had higher educational attainment, lower household income, and were more likely to receive 10 or more treatments in the past 12 months (odds ratio=5.39, 95% confidence interval=3.54, 8.22), compared to a nationally representative sample of U.S. acupuncture users. Self-reported health status and medical reasons for seeking acupuncture treatment were similar in both groups. Back pain (21%), joint pain (17%), and depression (13%) were the most common conditions for seeking treatment at community acupuncture clinics. CONCLUSIONS: Study findings suggest that local community acupuncture clinics reach individuals of a broad socioeconomic spectrum and may allow for increased frequency of treatment. Limited racial diversity among community acupuncture clients may reflect local demographics of Portland. In addition, exposure to and knowledge about acupuncture is likely to vary by race and ethnicity. Future studies should examine access, patient satisfaction, frequency of treatment, and clinical outcomes of group-based models of community acupuncture clinics located in racially and socioeconomically diverse communities.